Pengaruh Kesehatan dan Keselamatan Kerja (K3), Gaji dan Lingkungan Kerja terhadap Kinerja Karyawan pada CV Marga Jaya Tulungagung - Ilham Nur Intan Saida Hasanah; Miftahul Munir; Anita Sumelvia Dewi (Lembaga Pengembangan Kinerja Dosen, 2025)
The elements that need to be taken into account for ensuring successful employee perfomance are the degree of workplace safety and the work setting, as this is a crucial initiative that the company must implement to upload and offer a sense of security to its employees while carrying out their tasks. Furthermore, that salary policy is an essential element since salary serves as an indicator of employees motivation to fulfill their requirements. This research intends to ecaluate and examine the impact of occupational health and safety (K3), salary, and work environment on employee performance both individually and collectively. This research emplys a quantitative methodology featuring associative research. The data analysis technique used was multiple linear regression analysis using the SPSS version 25 program. The results of the study showed that occupational health and safety (K3) partially had a significant effect on employee performance with a tcal value of 3,465 > a ttable of 1,697. Salary partially has a significant effect on employee performance with a tcal value of 10,312 > ttable 1,697 and the work environment also has a significant effect on employee performance with a tcal value of 3,824 > ttable 1,697. The results of the hypothesis test simultaneously proved that occupational health and safety (K3), salary and work environment had a significant effect on employee performance with a calculated value of 82,825 > ftable 2.91.